Maternal Fructose Consumption Disrupts Brain Development of Offspring in a Murine Model of Autism Spectrum Disorder - Saad, Antonio F.; Alshehri, Wael; Lei, Jun; Kechichian, Talar B.; Gamble, Phyllis; Alhejaily, Nader; Shabi, Yahya; Saade, George R.; Costantine, Maged M.; Burd, Irina (American Journal of Perinatology, 2016)
Objective The objective of this study was to localize by neuroimaging the altered structural brain development of these offspring using an autism model of transgenic mice lacking contactin-associated protein-like 2 (Cntnap2).Materials and Methods Pregnant dams were randomly allocated to fructose solution (10% W/V) as only drinking fluid or water. Cntnap2 heterozygous (+/−) offspring from each group were euthanized at 6 months of age and their whole brains evaluated by magnetic resonance imaging. T2-weighted images were acquired to evaluate the volumes of 29 regions of interest involved in autism spectrum disorder (ASD) pathogenesis. Whole brains were washed and processed for Nissl staining. Mann–Whitney U test and one-way analysis of variance were used for statistical analysis (significance: p < 0.05).Results The corpus callosum, anterior commissure, and caudate putamen were significantly smaller in Cntnap2 (+/−) male offspring exposed to fructose. No brain alterations were found in the female counterparts. Nissl staining of the caudate putamen revealed higher neuronal cell count in the male fructose offspring. Female group revealed an increase in caudate putamen neuronal cell count.Conclusion Metabolic dysregulation in pregnancy alters fetal brain development in genetically predisposed offspring. This is consistent with findings in human studies and supports the role of intrauterine factors in the etiology of autism.
Keywords: fructose; metabolism; pregnancy; brain; autism spectrum disorder; two-hit hypothesis; neuroimaging